TECHNOLOGY OF WORKING ON THE ART WORK IN PRIMARY SCHOOLS - Choriyeva Ulugoy Chirchik (Galaxy International Interdisciplinary Research Journal, 2021)
In working on a work of art and defining its main stages, the teacher considers the specific features of the work of art as a work of art and the level of preparation of students.